The construction of the intellectual field of the history of education and its contribution to Pedagogical Peace: An interdisciplinary perspective (2019)
In the present work, some of the results of the Postdoctoral Program (UPTC-Tunja) are preliminarily exposed, especially with regard to the construction of the intellectual field of the history of education and Pedagogical Peace (Marquardt et Al, 2019). Among the objectives, it seeks to analyze how this Intellectual Field was formed within the research groups Grupo Hisula-UPTC, Grupo Primo Levi de Justicia Social, Grupo Hedure (Universidad de Los Andes-Táchira, Venezuela), the Red Sociedad de Historia and Latin American Education (Shela), and the Comparative Constitutional CC Group (National University of Colombia). Methodologically, it is an interdisciplinary investigation, which takes up the guidelines of historiography,   ethnography, and bibliometric research, in order to determine which are the authors and works, where they publish, which are the national and international networks, among others. It is noted that the aim is not to exhaust the subject, but rather to encourage debate, on a subject in which it is necessary to undermine the fences of the disciplines to provide answers with a higher rate of social return.